A revision of the Neogene Conidae and Conorbidae (Gastropoda) of the Paratethys Sea - Harzhauser, Mathias; Landau, Bernard (Zootaxa, 2016)
The Miocene Conidae and Conorbidae of the central- and south-eastern European Paratethys Sea are revised. In total, 74 species are described of which 10 are new species and 5 are documented for the first time from Paratethyan localities. Species descriptions and delimitations are partly based on morphometric data. In addition, colour patterns are described for the first time for the majority of species. In respect to the ongoing discussion on the supraspecific treatment of extant Conidae, we strongly focus on generic allocations and provide a key for the genera as understood herein. Biogeographically, the larger part of the assemblage indicates affiliation with modern western African faunas as indicated by the occurrence of genera such as Lautoconus, Kalloconus, Monteiroconus and Pseudonoduloconus. The relationship with Indo-West Pacific faunas is comparatively low. The high alpha-diversities observed for localities in the Pannonian, Transylvanian and Vienna basins, with up to 44 species, is a marker of tropical conditions in the Paratethys Sea during middle Miocene times. Conasprella minutissima nov. sp., Kalloconus hendricksi nov. sp., Kalloconus letkesensis nov. sp., Kalloconus pseudohungaricus nov. sp., Lautoconus kovacsi nov. sp., Lautoconus pestensis nov. sp., Lautoconus quaggaoides nov. sp., Leporiconus paratethyianus nov. sp., Plagioconus breitenbergeri nov. sp. and Plagioconus bellissimus nov. sp. are described as new species; Conilithes eichwaldi nov. nom. is proposed as new name for Conus exiguus Eichwald, 1830 [non Lamarck, 1810].